Integrated weed management in soybean (Glycine max)* - SINGH, GURIQBAL (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during (kharif) 2004 at the Punjab Agricultural University, Ludhiana to find out effective weed management in soybean [Glycine max (L.) Merr.]. The pre-emergence applications of pendimethalin 0.45 kg/ha + hand weeding 30 days after sowing, clomazone 1 kg/ha + hand weeding 30 days after sowing, alachlor 2 kg/ ha, clomazone 1 kg/ha and 2 hand weedings at 30 + 45 days after sowing controlled weeds effectively and provided high grain yields of soybean. Uncontrolled weeds resulted in 40.2 and 42.3% yield reduction as compared to two hand weedings and the highest yield providing treatment respectively.